Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve the equation. Enter your answer in the box.

[tex]\[ -\frac{5}{6}e - \frac{2}{3}e = -24 \][/tex]

[tex]\( e = \)[/tex]


Sagot :

Let's solve the given equation step by step:

1. The original equation is:
[tex]\[ -\frac{5}{6}e - \frac{2}{3}e = -24 \][/tex]

2. Combine the like terms on the left-hand side (LHS). To do this, let's get a common denominator for the fractions. The common denominator of 6 and 3 is 6.
[tex]\[ -\frac{5}{6}e - \frac{4}{6}e = -24 \][/tex]

3. Now, combine the fractions:
[tex]\[ -\left(\frac{5}{6}e + \frac{4}{6}e\right) = -24 \][/tex]
[tex]\[ -\frac{9}{6}e = -24 \][/tex]

4. Simplify the fraction on the LHS:
[tex]\[ -\frac{3}{2}e = -24 \][/tex]

5. To isolate [tex]\( e \)[/tex], multiply both sides of the equation by the reciprocal of [tex]\(-\frac{3}{2}\)[/tex], which is [tex]\(-\frac{2}{3}\)[/tex]:
[tex]\[ e = -24 \times \left(-\frac{2}{3}\right) \][/tex]

6. Perform the multiplication:
[tex]\[ e = 16 \][/tex]

Therefore, the solution to the equation is:
[tex]\[ e = 16 \][/tex]